1998
DOI: 10.1046/j.1523-1747.1998.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of the IL-2 Receptor β Chain for the Development of Vγ3 Dendritic Epidermal T Cells

Abstract: Vgamma3 TCR cells develop in the fetal thymus and migrate to the skin as dendritic epidermal T cells (DETC). Fetal Vgamma3 thymocytes differentiate from immature heat stable antigen (HSA)high cells to mature HSAlow cells and the latter subset predominantly expresses IL-2 receptor beta chain (IL-2Rbeta). In this study, the role of IL-2Rbeta in the development of Vgamma3 cells was determined in IL-2Rbeta-deficient mice. There was a moderate reduction of mature HSAlow Vgamma3 thymocytes in IL-2Rbeta-deficient mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 49 publications
3
41
0
Order By: Relevance
“…However, recent studies showed that enforced expression of Bcl-2 did not restore TCR␥␦ IEL in the skin of not only IL-2/15R␤ KO mice but also V␥5/V␦1 TCR-transgenic IL-2/15R␤ KO mice (44), suggesting that TCR␥␦ s-IEL most likely receive proliferation and survival signals from IL-15 independently of Bcl-2. In support of this, it was shown that exogenous addition of IL-15 to organ culture of fetal skin induced proliferation of V␥5 s-IEL (45). Similar to the case with TCR␥␦ s-IEL, enforced expression of Bcl-2 did not restore the number of NKT cells in IL-15 KO mice.…”
Section: Discussionmentioning
confidence: 85%
“…However, recent studies showed that enforced expression of Bcl-2 did not restore TCR␥␦ IEL in the skin of not only IL-2/15R␤ KO mice but also V␥5/V␦1 TCR-transgenic IL-2/15R␤ KO mice (44), suggesting that TCR␥␦ s-IEL most likely receive proliferation and survival signals from IL-15 independently of Bcl-2. In support of this, it was shown that exogenous addition of IL-15 to organ culture of fetal skin induced proliferation of V␥5 s-IEL (45). Similar to the case with TCR␥␦ s-IEL, enforced expression of Bcl-2 did not restore the number of NKT cells in IL-15 KO mice.…”
Section: Discussionmentioning
confidence: 85%
“…Liver lymphocytes, intestinal IEL, and epidermal cells were prepared as described previously (27,70,71). …”
Section: Cell Preparationmentioning
confidence: 99%
“…Diluted cDNA was amplified by PCR using primers specific for TCR V␣14-J␣281 (74). The amount of template cDNA was normalized using primers for ␤-actin (27).…”
Section: Rt-pcrmentioning
confidence: 99%
See 2 more Smart Citations